KONVERSI AGAMA : FAKTOR DAN PROSES TERJADINYA - Fadhilah Wardatul Muslimah; Siti Rochimah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Religious conversion is a complex process involving both psychological and spiritual dimensions. This article aims to explore the factors, stages, and impacts of religious conversion within the framework of Islamic educational psychology. The study employs a qualitative descriptive approach through library research. The findings indicate that religious conversion typically progresses through five psychological stages and is influenced by various factors including social relationships, personal experiences, institutional dynamics, and life crises. This research highlights the significance of holistic and inclusive Islamic education in addressing the phenomenon of religious conversion, positioning it not merely as a shift in belief but as a reflection of one’s inner spiritual journey.